2014
DOI: 10.1007/s00701-014-2081-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine but risky: A multi-centre analysis of the outcomes of cranioplasty in the Northeast of England

Abstract: Cranioplasty harbours significant morbidity, a risk that appears to be higher with a bifrontal defect. The complications experienced influence subsequent functional outcome. The timing of cranioplasty, early or late, after the initial operation does not impact on the ultimate outcome. These findings should be considered when making decisions relating to craniectomy and cranioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 47 publications
4
56
0
3
Order By: Relevance
“…3,9,20,26 Within the Western Australian statewide neurosurgical service, the overall infection rate for cranial procedures has been consistently audited at 1%-2%; however, our previous studies have also demonstrated a high cranioplasty infection rate, consistent with some other reports. 13,17 It is unknown why it is so high; a number of reasons have been proposed, including skin colonization while in the hospital, uncertain sterility with long-term storage of the bone flap, and reduced immune response following major brain injury trauma and reop- eration.…”
Section: Infectionsupporting
confidence: 84%
“…3,9,20,26 Within the Western Australian statewide neurosurgical service, the overall infection rate for cranial procedures has been consistently audited at 1%-2%; however, our previous studies have also demonstrated a high cranioplasty infection rate, consistent with some other reports. 13,17 It is unknown why it is so high; a number of reasons have been proposed, including skin colonization while in the hospital, uncertain sterility with long-term storage of the bone flap, and reduced immune response following major brain injury trauma and reop- eration.…”
Section: Infectionsupporting
confidence: 84%
“…The study found that the incidence of SSI in cranioplasty using the autologous bone flap method at the two studied centres was 5.9% in 101 patients within a period of 18 months. This finding is consistent with previously reported rates of infection, ranging between 7% and 22% (10)(11). The rate of postcranioplasty SSI was 5.5% and 6.5% for the cryopreserved bone flaps and the bone flaps stored in the abdominal subcutaneous pocket, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Though CP is a regular surgery, it has many complications, including CNS infection, hydrocephalus, intracranial hematoma and subdural fluid collection, which will prolong the hospitalization, lead to unfavorable prognosis and even death [11]. Because of the allograft materials implantation, the risk of infection is relatively magnified in CP compared with other neurosurgical operations.…”
Section: Discussionmentioning
confidence: 99%
“…Decompressive craniotomy (DC) -a surgical procedure that involves the removal of part of the skull to accommodate brain swelling -has been used for many years in the management of patients with brain edema and/or intracranial hypertension due to subarachnoid hemorrhage, traumatic brain injury, cerebral infarction, intracerebral hemorrhage (ICH), and other causes [1,11,18,20]. Since more patients survive because of the DC surgery, the number of subsequent cranioplasty (CP) procedures is increasing.…”
Section: Introductionmentioning
confidence: 99%